The Integration of Religious Pluralism into Teacher Preparation (Journal of Advanced Research in Social Sciences, 2024)
Preparing future teachers for their roles in classrooms is growing ever more challenging. Concerns involving safety, salaries, and overall respect for the profession have created an emerging shortage in licensed teachers, one that has parents concerned and politicians paying attention. Despite the barriers to recruitment, the quest to train and support the most effective teacher workforce continues, buffered by opportunities to serve a diverse student population and to close ever-widening opportunity and achievement gaps. Racial, ethnic, and language diversity makes the United States a rich mosaic of cultures, but it can often be the religious differences of students and parents that raise very unique challenges in providing equity and acceptance for all. Part of what makes a 21st century educator effective is the ability to appreciate differences in culture, worldview, and ethnicity. As such, the exploration of religious pluralism and the integration of such into our education curriculum, instruction and dialogue has now become a major area of focus at a school of Education in the southeast United States. Preparing future teachers for the difference in religious views that may be experienced in their own classroom is now part of how we approach teacher preparation. By integrating religion-centered role play and simulations into our teaching, this research focused on providing teacher candidates with valuable tools through which to be prepared for diverse classrooms. As part of our study and efforts, student surveys and data were collected to analyze the impact and the work moving forward.